Automated testing in robotic process automation projects. Issue 3 (17th March 2020) - Jiménez‐Ramírez, Andres; Chacón‐Montero, Jesús; Wojdynsky, Tomasz; González Enríquez, José
Abstract : Robotic process automation (RPA) has received increasing attention in recent years. It enables task automation by software components, which interact with user interfaces in a similar way to that of humans. An RPA project life cycle is closely resembling a software project one. However, in certain contexts (e.g., business process outsourcing), a testing environment is not always available. Thus, deploying the robots in the production environment entails high risk. To mitigate it, an innovative approach to automatically generate a testing environment and a test suite for an RPA project is presented. The activities of the humans whose processes are to be robotized are monitored and a UI log is confirmed. On one side, the test environment is generated as a fake application, which mimics the real environment by leveraging the UI log information. The control flow of the application is governed by an invisible control layer that decides which image to show depending on the interface actions that it receives. On the other side, the test case checks whether the robot can reproduce the behaviour of the UI log. Promising results were obtained and a number of limitations were identified such that it may be applied in more realistic domains. Abstract : Monitoring user activities enables a deep analysis of an Information System (IS) and the robots that are to be implemented to interact with it. This paper proposes the automatic construction of fake IS which can be used to test the robot's behaviour before it is deployed to the real IS. This automatic early testing aims to improve the analysis and design of the first releases of the robot.